Penerapan Dana Reguler Kelompok Simpan Pinjam Perempuan Pada PNPM-MPD Di Kecamatan Wangon, Kabupaten Banyumas - Widodo, Taufik Margi; Ramadhanti, Wita; Rokhayati, Hijroh (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2017)
The implementation of society empowerment, especially in the form of revolving funds (saving and loan) that consider less is financial management, and guidance on life skills that are able to support women business group. Through one of its program Women Saving and Loan / Simpan Pinjam Perempuan (SPP), it is expected to improve the welfare of people, especially womenand also applied poverty alleviation mechanism involving elements of society, start from planning, implementation, control and evaluation stages. The purpose of this studys are to determine the significance of differences revenue (financial performance) and the welfare of the group before and after the SPP program of National Program for (Rural) Society Empowerment / Program Nasional Pemberdayaan masyarakat Mandiri Perdesaan PNPM-MPd. These study used comparative technique bases on mix method with research object are SPP groups in Wangon Sub-District, Banyumas District. Hypothesis is tested by using non-parametric test through wilcoxon test and in-depth interviews. The results showed that there is an increase in revenue and welfare level, which means there are differences in revenue and welfare level before and after join the SPP program.